Quality of clinical evidence and political justifications of ivermectin mass distribution of COVID-19 kits in eight Latin American countries - Veronika J Wirtz; Dolores Mino-León; José Antonio Requejo Domínguez (BMJ Global Health)
Background Several countries in Latin America conducted mass distribution of COVID-19 kits intended to treat mild COVID-19, thereby preventing excess hospitalisations. Many of the kits contained ivermectin, an antiparasitic medicine that was not approved at the time for the treatment of COVID-19. The study objective was to compare the timing of the publication of scientific evidence about the efficacy of ivermectin for COVID-19 with the timeline of distribution of COVID-19 kits in eight Latin American countries and to analyse whether evidence was used to justify ivermectin distribution.Methods We conducted a systematic review of randomised controlled trials (RCTs) published on the efficacy of ivermectin or ivermectin as adjuvant therapy on mortality from, or as prevention for, COVID-19. Each RCT was assessed using the Cochrane Grading of Recommendations, Assessment, Development and Evaluations (GRADE). Information on the timing and justification of government decisions was collected through a systematic search of leading newspapers and government press releases.Results After removing the duplicates and abstracts without full text, 33 RCTs met our inclusion criteria. According to GRADE, the majority had a substantial risk of bias. Many government officials made claims that ivermectin was effective and safe in the prevention or treatment of COVID-19, despite the lack of published evidence.Conclusion All eight governments distributed COVID-19 kits to their populations despite the absence of high-quality evidence on the efficacy of ivermectin for prevention, hospitalisation and mortality in COVID-19 patients. Lessons learnt from this situation could be used to strengthen government institutions’ capacities to implement evidence-informed public health policies.